2007
DOI: 10.1073/pnas.0700774104
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast iron-sulfur cluster protein maturation requires the essential cysteine desulfurase CpNifS

Abstract: NifS-like proteins provide the sulfur (S) for the formation of iron-sulfur (Fe-S) clusters, an ancient and essential type of cofactor found in all three domains of life. Plants are known to contain two distinct NifS-like proteins, localized in the mitochondria (MtNifS) and the chloroplast (CpNifS). In the chloroplast, five different Fe-S cluster types are required in various proteins. These plastid Fe-S proteins are involved in a variety of biochemical pathways including photosynthetic electron transport and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 48 publications
6
62
1
Order By: Relevance
“…1, 3, and 4). RNAi lines induced for loss of NFS2 or SufBCD complex components had shown a general loss of all Fe-S proteins, including strong effects on PSI subunits PSAA, and PSAB on GOGAT (Van Hoewyk et al, 2007;Hu et al, 2017b). However, we did not see this general loss of plastid Fe-S cluster proteins for Fe deficiency.…”
Section: Iron Economy Involves Specific Response Programscontrasting
confidence: 41%
See 1 more Smart Citation
“…1, 3, and 4). RNAi lines induced for loss of NFS2 or SufBCD complex components had shown a general loss of all Fe-S proteins, including strong effects on PSI subunits PSAA, and PSAB on GOGAT (Van Hoewyk et al, 2007;Hu et al, 2017b). However, we did not see this general loss of plastid Fe-S cluster proteins for Fe deficiency.…”
Section: Iron Economy Involves Specific Response Programscontrasting
confidence: 41%
“…Therefore, at least some of the observed effects seem to be caused by Fe deficiency proper and not just by downstream defects due to lack of cofactor assembly. We can also compare consequences of Fe deficiency at the molecular level with effects caused by genetically induced loss of Fe-S assembly factors NFS2 (Van Hoewyk et al, 2007) and SUF-BCD (Hu et al, 2017a(Hu et al, , 2017b. Loss via RNAi of NFS2 activity (Van Hoewyk et al, 2007) or SUF-BCD activity (Hu et al, 2017b) caused physiological effects after 1 week that are very similar to the Fe deficiency described here (Figs.…”
Section: Iron Economy Involves Specific Response Programsmentioning
confidence: 83%
“…In Arabidopsis, two distinct NifS proteins exist, localized to the chloroplast and mitochondria (CpNifS and MtNifS, respectively). Recently, a study employing a CpnifS mutant has shown that the protein is essential for the maturation of plastidic Fe-S proteins (35). As THIC is localized to the chloroplast, we examined both THIC abundance and thiamin content in the CpnifS mutant.…”
Section: Regulatory Mechanisms Revealed By Expression Analysismentioning
confidence: 99%
“…Plant cytosol contains homologs of the cytosolic Fe-S assembly proteins that have recently been identified in yeast (Lill and Mü hlenhoff, 2008), including the scaffold protein AtNBP35 (Bych et al, 2008;Kohbushi et al, 2009) and the hydrogenase-like AtNAR1 (Cavazza et al, 2008). It is thought that cytosolic Fe-S cluster assembly is dependent on at least one of the organelles, because the Cys desulfurases that generate sulfur for Fe-S clusters, CpNifS and NFS1, are strictly localized in the plastids and mitochondria, respectively (Kushnir et al, 2001;Frazzon et al, 2007;Van Hoewyk et al, 2007).…”
mentioning
confidence: 99%